Cadmium induced BEAS-2B cells apoptosis and mitochondria damage via MAPK signaling pathway. (January 2021) - Cao, Xiangyu; Fu, Mingyang; Bi, Ruochen; Zheng, Xiaomei; Fu, Baorong; Tian, Siqi; Liu, Chengying; Li, Qijiu; Liu, Jianli
Abstract: Cadmium, a heavy metal pollutant in industrial production, is found in air, water and soil, which is harmful to human health and can lead to diseases, such as asthma, lung cancer, and emphysema. In this study, the toxicity of cadmium on human bronchial epithelial cells (BEAS-2B) was investigated. Cell viability, mitochondrial membrane potential, reactive oxygen species (ROS) level, apoptosis and the related signaling pathways were detected with MTT assay, Rhodamine staining, DCFH-DA staining, Hoechst33258 staining and Western blot methods respectively. The results showed that the cell viability decreased, the mitochondrial membrane potential declined, ROS was accumulated and apoptotic rate raised in BEAS-2B cells. Meanwhile, the expression of B-cell lymphoma-2 (Bcl-2) was downregulated, while the expression of Bcl-2-associated X protein (Bax) and the cleaved caspase-3 was upregulated, which indicated mitochondria-mediated intrinsic apoptosis pathway was activated. Furthermore, the phosphorylation of JNK, ERK and p38 was enhanced respectively, which manifested that MAPK signaling pathways were activated. Therefore, it could be concluded that cadmium could increase intracellular ROS, result in cellular oxidative stress, activate JNK, ERK and p38 MAPK pathways and ultimately lead to apoptosis of BEAS-2B cells by activating mitochondria-mediated intrinsic apoptosis pathway. This study provided useful information to elucidate the toxicity of cadmium and revealed the possible mechanism for the occurrence of lung disease induced by cadmium. Graphical abstract: Cadmium increased the reactive oxygen species (ROS) generation, induced cell apoptosis and activated MAPK cell signaling pathway. Meanwhile, cadmium accelerated mitochondria damage and activated mitochondria-mediated intrinsic apoptosis pathway in BEAS-2B cells. Image 1 Highlights: Cadmium induced the accumulation of ROS and cell apoptosis in BEAS-2B. Cadmium activated MAPK pathways, including JNK, ERK and p38 MAPK. Cadmium decreased mitochondrial membrane potential, activated the apoptosis pathway.